Proceedings of the international symposium on frontiers of science : (World scientific, 2003)
The International Symposium on Frontiers of Science was held to celebrate the 80th birthday of Chen Ning Yang, one of the great physicists of the 20th century and arguably the most-admired living scientist in China today. Many of the world’s great scientists — including sixteen Nobel laureates, Fields medallists and Wolf Prize winners — converged on Beijing from all corners of the globe to pay tribute to Professor Yang. The Symposium was organized by Tsinghua University, with which Professor Yang has had a lifelong relationship. In 1997, he helped to found the Center for Advanced Study at Tsinghua, was appointed to the university’s faculty, and has since devoted his energy to the growth of the Center. This unique and invaluable birthday volume is a collection of the presentations made at the Symposium, including fifteen plenary talks, seven of which are by Nobel laureates. It covers a wide range of topics and mirrors Professor Yang’s research and intellectual interests. The range of fields encompasses high-energy, condensed-matter, mathematical, applied, bio-, astro-, atomic and quantum physics. Also included are talks given at the birthday banquet.